2019
DOI: 10.1002/pssb.201900205
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Study of Metal Atoms Adsorption on 2D Dumbbell C4N

Abstract: Similar to graphene, zero bandgap is found in the recently proposed 2D dumbbell C4N (DB C4N), which limits its applications as electronic devices. Surface adsorption effectively modifies the electronic and magnetic properties of the 2D materials. Herein, the adsorption behaviors of 16 metal atoms adsorbed on the DB C4N, including alkali metals, alkaline earth metals, 3d transition metals (TMs), and precious metals, are investigated using the density functional theory. The electronic and magnetic properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Reproduced with permission from Ref. [ 30 ]. l Top (upper) and side (lower) view of the atomic structure of C 5 N monolayer.…”
Section: Cnbmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission from Ref. [ 30 ]. l Top (upper) and side (lower) view of the atomic structure of C 5 N monolayer.…”
Section: Cnbmsmentioning
confidence: 99%
“…Bhuriyal et al also reported the first-principle study of C 3 N monolayer as a promising anode material for SIBs and PIBs, and they showed that multilayer adsorption of the metal atoms generated a high capacity of 1072 mAh g −1 and low diffusion barrier of 0.03 and 0.07 eV for Na and K-ion [ 55 ]. Xu et al showed that metal ion (Li, Na, and K) adsorption on C 4 N is an effective way to open the zero bandgap and modulate the electronic property because the adsorbed metal ion transfers charges to the surface of DB C 4 N [ 30 ].…”
Section: Dft-guided Studies Of Cnbms For Energy Storage Devicesmentioning
confidence: 99%
“…The calculations were performed using the Vienna Ab initio Simulation Package (VASP), with the projector-augmented wave (PAW) method , considering the spin polarization. The Perdew–Burke–Ernzerhof (PBE) functional including van der Waals corrections (PBE-TS) was employed, as this functional has been used to calculate the charge transfer between adatoms and vdW materials. ,,,, The plane-wave cutoff energy was set to 550 eV. The Brillouin zones of the unit cell of the bulk vdW materials were sampled with a 15 × 15 × 7 Γ-centered Monkhorst-Pack k -point mesh .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The Perdew−Burke−Ernzerhof (PBE) 43 functional including van der Waals corrections (PBE-TS) 44 was employed, as this functional has been used to calculate the charge transfer between adatoms and vdW materials. 25,26,30,37,45 The plane-wave cutoff energy was set to 550 eV. The Brillouin zones of the unit cell of the bulk vdW materials were sampled with a 15 × 15 × 7 Γ-centered Monkhorst-Pack k-point mesh.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation